2016
DOI: 10.1027/0269-8803/a000164
|View full text |Cite
|
Sign up to set email alerts
|

Slow Wave Activity Related to Working Memory Maintenance in the N-Back Task

Abstract: Abstract. Working memory supports our ability to maintain goal-relevant information that guides cognition in the face of distraction or competing tasks. The N-back task has been widely used in cognitive neuroscience to examine the functional neuroanatomy of working memory. Fewer studies have capitalized on the temporal resolution of event-related brain potentials (ERPs) to examine the time course of neural activity in the N-back task. The primary goal of the current study was to characterize slow wave activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 44 publications
2
11
1
Order By: Relevance
“…The role of maintenance in neuronal mechanisms of WM training: Our study tested the hypothesis that WM training would lead to more effective maintenance of the to-beremembered stimuli, as reflected by changes in slow waves occurring during active maintenance of WM contents (Bailey et al 2016, Vilà-Balló et al 2018. In accordance to our expectations, NSW was indeed affected by training.…”
Section: Running Head: Updating Training Modulates Erpssupporting
confidence: 74%
See 4 more Smart Citations
“…The role of maintenance in neuronal mechanisms of WM training: Our study tested the hypothesis that WM training would lead to more effective maintenance of the to-beremembered stimuli, as reflected by changes in slow waves occurring during active maintenance of WM contents (Bailey et al 2016, Vilà-Balló et al 2018. In accordance to our expectations, NSW was indeed affected by training.…”
Section: Running Head: Updating Training Modulates Erpssupporting
confidence: 74%
“…In humans, slow negative components (NSW) persisting throughout the retention interval in WM tasks predict the number of objects to be maintained in memory (Fukuda et al 2010, Luria et al 2016. A slow wave related to active maintenance of WM contents between n-back trials has been reported in a few prior studies (Bailey et al 2016, Vilà-Balló et al 2018. There is evidence that also the amplitude of the contingent negative variation (CNV, Walter et al, 1964) during the retention interval is smaller when the memory load is higher (Ford et al 1979;Roth et al 1975;Roth et al 1978), but this response can be distinguished from the other slow waves based on its scalp distribution (e.g., McEvoy et al 1998).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations